Why the tremendous potential of uploading health educational material on medical institutions' website remains grossly underutilized in the era of the Fourth Industrial Revolution? - Sudip Bhattacharya; Amarjeet Singh (Wolters Kluwer Medknow Publications, 2020)
Due to the short span available for consultation with clinicians, patients try to become well versed with their clinical conditions before the medical consultation. They search Google for their medical information; here comes the problem of authenticity of the sources. It is very difficult to obtain authentic medical information for the patients from the Internet. As a result, sometimes, patients ask questions to the overburdened doctors and irritate them. To solve this problem and wider dissemination of authentic medical knowledge, the existing website of Post Graduate Institute of Medical Education and Research (PGIMER) has been utilized. In PGIMER, Chandigarh, health education materials in text and video formats have been uploaded on the PGIMER website for empowering patients. All these have been successfully tested in the outpatient departments of PGIMER, Chandigarh. To our knowledge, this unique approach is the first of its kind in India. We hope this approach of sharing medical information through the PGIMER website may help patient empowerment to a large extent. Later, this concept can be replicated in all medical colleges in India.